Recent trends in cataract management - Espaillat, Arnaldo; Agarwal, Amar (Panamá : Highlights of ophthalmology, 2013)
Este libro es todo lo que usted podría desear de un libro médico y más: contenido altamente educativo, bellas ilustraciones y fotografías didácticas, diseño visualmente atractivo y un estilo excelente.
CONTENIDO Chapter 1. Preoperative selection for cataract surgery Chapter 2. Optimizing refractive outcome: surgical correction of astigmatism cataract Chapter 3. IOL Power calculation in standard and complex cases Chapter 4. Dynamic Chapter 5. Transition y otros
Incluye índice de temas
Keywords: CATARACT; OFTALMOLOGÍA